Erosi Paradise: Dampak Konversi Lahan Pertanian dan Privatisasi Ruang Publik terhadap Pariwisata yang Tidak Berkelanjutan di Bali - Putu Ayu Sita Laksmi; Komang Adi Kurniawan Saputra (Lembaga Penelitian, Universitas Warmadewa, 2026)
Bali is experiencing massive conversion of agricultural land and privatisation of public space, threatening tourism sustainability. This study aims to deeply understand the lived experiences of local communities and tourists regarding the impact of these phenomena on unsustainable tourism. Using a transcendental phenomenological qualitative approach, data were collected through in-depth interviews, participant observation, and document analysis with 23 informants consisting of farmers, traditional leaders, repeat tourists, micro-enterprise owners, and environmental activists in Badung, Tabanan, and Gianyar regencies. The findings reveal three major themes: the loss of rice fields as the motherland and source of life; public space transformed into walls of exclusivity; and tourism that feels foreign in one's own homeland. Land conversion does not only cause economic loss but also symbolic death, ecological alienation, ontological crisis, and structured spatial injustice through bureaucratic corruption. Privatisation of public space marginalises the grassroots economy and erodes tourists' experiences in seeking authenticity. This study concludes that sustainable tourism in Bali is impossible to achieve without agrarian reform, strengthening of customary law, and enforcement of spatial justice. The findings contribute to the overtourism literature by emphasising equitable spatial governance as a prerequisite for sustainability.